Modulating factors of the abundance and distribution of Achelous spinimanus (Latreille, 1819) (Decapoda, Portunoidea), a fishery resource, in Southeastern Brazil - De Sousa, Aline Nonato [UNESP]; Bertini, Giovana [UNESP]; Taddei, Fabiano Gazzi [UNESP]; Da Costa, Rogério Caetano [UNESP]; Da Silva, Thiago Elias [UNESP]; Fransozo, Adilson [UNESP] (PeerJ, 2018)
This is the first study to examine how different environmental factors may influence the distribution of swimming crab Achelous spinimanus across geographically distant and distinct habitats. We analyzed the influence of bottom water temperature and salinity, sediment texture and organic matter content on the spatiotemporal distribution of A. spinimanus. The crabs were collected from January 1998 until December 1999 by trawling with a shrimp fishing boat outfitted with double-rig nets. The sampling took place in Ubatumirim (UBM), Ubatuba (UBA) and Mar Virado (MV) bays, located in the northern coast of São Paulo State (Brazil). These three bays were chosen as they differed in many physiographic features. We captured 1, 911 crabs (UBM = 351; UBA = 1, 509; MV = 51), and there were significant differences in abundance between bays and between stations. The distribution of A. spinimanus was primarily associated with sediment features: abundance was higher in stations with sandy sediments classified as gravel, very coarse sand, and intermediate sand. Portunoidea usually burrow in the sediment for protection against predators and to facilitate the capture of fast prey. In addition, the station with the highest abundance of A. spinimanus was also naturally protected from fishing activities, and composed of heterogeneous sediment, in terms of grain size. Hence, the combination of a favorable sediment heterogeneity and protection from fishery activities seemed to be effective modulators of the abundance and distribution of A. spinimanus in these bays.
Keywords: Fishing activity; Portunoidea; Sediment; Spatiotemporal distribution; Ubatuba; Water mass